Information Seeking and Sharing in Design Teams - Poltrock, Steven; Grudin, Jonathan; Dumais, Susan; Fidel, Raya; Bruce, Harry; Pejtersen, Annelise Mark (Proceedings of the Conference on Supporting Group Work (Group 2003), 2003)
Information retrieval is generally considered an individual activity, and information retrieval research and tools reflect this view. As digitally mediated communication and information sharing increase, collaborative information retrieval merits greater attention and support. We describe field studies of information gathering in two design teams that had very different products, disciplinary backgrounds, and tools. We found striking similarities in the kinds of information they sought and the methods used to get it. For example, each team sought information about design constraints from external sources. A common strategy was to propose ideas and request feedback, rather than to ask directly for recommendations. Some differences in information seeking and sharing reflected differences in work contexts. Our findings suggest some ways that existing team collaboration tools could support collaborative information retrieval more effectively.